2021
DOI: 10.1186/s12974-021-02327-4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating expression of OPTN elevates neuroinflammation via AIM2 inflammasome- and RIPK1-activating mechanisms in APP/PS1 transgenic mice

Abstract: Background Neuroinflammation is thought to be a cause of Alzheimer’s disease (AD), which is partly caused by inadequate mitophagy. As a receptor of mitophagy, we aimed to reveal the regulatory roles of optineurin (OPTN) on neuroinflammation in the pathogenesis of AD. Methods BV2 cells and APP/PS1 transgenic (Tg) mice were used as in vitro and in vivo experimental models to determine the regulatory roles of OPTN in neuroinflammation of AD. Sophistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…We identified differences in the expression of OPTN during the development of IVDD and changes in the expression of OPTN in NPCs subjected to oxidative stress and explored the impact of changes in OPTN expression on NPCs and the potential for OPTN as a therapeutic target for IVDD. We found that the expression of OPTN markedly decreased as IVDD was exacerbated, which is consistent with findings related to the expression of OPTN in degenerative diseases ( Cao et al, 2021 ) and the expression of other mitophagy-related genes in the intervertebral disc ( Chen et al, 2020 ; Hu et al, 2021a ). OPTN expression was substantially increased in cells treated with H 2 O 2 compared with untreated control cells.…”
Section: Discussionsupporting
confidence: 90%
“…We identified differences in the expression of OPTN during the development of IVDD and changes in the expression of OPTN in NPCs subjected to oxidative stress and explored the impact of changes in OPTN expression on NPCs and the potential for OPTN as a therapeutic target for IVDD. We found that the expression of OPTN markedly decreased as IVDD was exacerbated, which is consistent with findings related to the expression of OPTN in degenerative diseases ( Cao et al, 2021 ) and the expression of other mitophagy-related genes in the intervertebral disc ( Chen et al, 2020 ; Hu et al, 2021a ). OPTN expression was substantially increased in cells treated with H 2 O 2 compared with untreated control cells.…”
Section: Discussionsupporting
confidence: 90%
“…In the late stage of APP/PS1 mouse models, astrocytes also triggered immune signaling and lack of neuroprotection (Orre et al, 2014). Reactive astrocytes induced neuroinflammation and activated the transcriptional activity of NF-κB to induce inflammatory factors (Cao et al, 2021; Figure 2).…”
Section: Apolipoprotein E and Astrocytesmentioning
confidence: 99%
“…Peripheral cells released signal factors to recruit extra cells from the periphery and maintain the activation of microglia and astrocytes, leading to excessive activation of astrocytes, which further damaged surrounding tissues and neurons (Gyoneva and Ransohoff, 2015 ). Additionally, secondary inflammation after CNS injury is the body’s reactive inflammation to the injury, which is different from primary neuroinflammation, such as AD, which is caused by the disorder of normal growth and metabolism in cells (Cao et al, 2021 ).…”
Section: Astrocyte Activation After Injurymentioning
confidence: 99%